DYRK1a Inhibitor Mediated Rescue of Drosophila Models of Alzheimer’s Disease-Down Syndrome Phenotypes - Zhu, Bangfu; Parsons, Tom; Stensen, Wenche; Mjøen Svendsen, John S.; Fugelli, Anders; Hodge, James J. L. (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is the most common neurodegenerative disease which is becoming increasingly prevalent due to ageing populations resulting in huge social, economic, and health costs to the community. Despite the pathological processing of genes such as Amyloid Precursor Protein (APP) into Amyloid- and Microtubule Associated Protein Tau (MAPT) gene, into hyperphosphorylated Tau tangles being known for decades, there remains no treatments to halt disease progression. One population with increased risk of AD are people with Down syndrome (DS), who have a 90% lifetime incidence of AD, due to trisomy of human chromosome 21 (HSA21) resulting in three copies of APP and other AD-associated genes, such as DYRK1A (Dual specificity tyrosine-phosphorylation-regulated kinase 1A) overexpression. This suggests that blocking DYRK1A might have therapeutic potential. However, it is still not clear to what extent DYRK1A overexpression by itself leads to AD-like phenotypes and how these compare to Tau and Amyloid-Beta mediated pathology. Likewise, it is still not known how effective a DYRK1A antagonist may be at preventing or improving any Tau, Amyloid-Beta and DYRK1a mediated phenotype. To address these outstanding questions, we characterised Drosophila models with targeted overexpression of human Tau, human Amyloid-Beta or the fly orthologue of DYRK1A, called minibrain (mnb). We found targeted overexpression of these AD-associated genes caused degeneration of photoreceptor neurons, shortened lifespan, as well as causing loss of locomotor performance, sleep, and memory. Treatment with the experimental DYRK1A inhibitor PST-001 decreased pathological phosphorylation of human Tau (at serine (S) 262). PST-001 reduced degeneration caused by human Tau, Amyloid-Beta or mnb lengthening lifespan as well as improving locomotion, sleep and memory loss caused by expression of these AD and DS genes. This demonstrated PST-001 effectiveness as a potential new therapeutic targeting AD and DS pathology.